From Urban Renewal to the BeltLine: Atlanta's Use of Public Health Narratives to Reshape the City. (February 2022) - OConnell, L. Katie; Botchwey, Nisha
Since the early days of the planning profession, city agencies relied on a public health crisis narrative as a rationale for mass displacement efforts that targeted black communities. Over time, as cities gentrified with white, middle-class residents, the narrative shifted toward the city as a place of health. This article compares Atlanta's redevelopment narratives from urban renewal to its current citywide greenway project, the BeltLine, to understand how city officials utilized public health language to rationalize displacement and how the narratives ran counter to residents' lived experience.